(untitled) (Global Journal of Management and Business Research, 2021)
Regarding the challenges of global digitization and network technology whether traditional media and new media are a game or a topic of integration has attracted much attention in recent years It has become a research hotspot for scholars at home and abroad With the constant emergence of various new media the pattern of mass communication is undergoing tremendous changes and traditional media have also begun their way of media integration In this regard this article takes the Shanghai World Expo news report as the starting point and deeply studies the exploration and practice of new media technology by traditional media in the World Expo report Also analyzed the streaming media other new media technologies paths and effects This paper declares that the development of new media is changing traditional media s communication methods and concepts Under the background of the vigorous development of new media traditional media must adapt to the needs of new media change their strengths and pursue news planning and in-depth reporting It has been proved that traditional media will not weaken through the bonding and interaction with new media With the advantages of new media traditional media can also enhance brand influence and popularity